International Classification of Functioning, Disability and Health and Clinical Education. - Papathanasiou, Ilias (Perspectives of the ASHA Special Interest Groups, 2018)
Purpose: In this article, we will describe the principles of applying the International Classification of Functioning, Disability and Health (ICF) framework in the education of communication sciences and disorders programs. Conclusion: ICF should be introduced to students as early as possible and can also be used as a framework to develop course curriculum as well as clinical competencies. Finally, ICF as an approach can be used in interprofessional education.